2022
DOI: 10.7759/cureus.23123
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Stroke and Factors Associated With It Among Old Age Hypertensive Patients in Karachi, Pakistan: A Cross-Sectional Study

Abstract: Introduction: Worldwide, stroke has become the major cause of mortality and morbidity among the old age population. Hypertension is one of the factors associated with stroke. Individuals with hypertension are at high risk of developing stroke. This study was conducted to determine the frequency of stroke factors associated with it among old-age hypertensive patients in Karachi, Pakistan.Methods: It was a cross-sectional study conducted in outpatient departments (OPD) of two tertiary care hospitals of Karachi, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Ischemic stroke can be either embolic or thrombotic [16]. In Pakistan, and ischemic and hemorrhagic type proportions are 70.1% and 29.9% [17,18]. A previous study reported that ischemic stroke can be caused by several fixed and modified risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke can be either embolic or thrombotic [16]. In Pakistan, and ischemic and hemorrhagic type proportions are 70.1% and 29.9% [17,18]. A previous study reported that ischemic stroke can be caused by several fixed and modified risk factor.…”
Section: Discussionmentioning
confidence: 99%